2017
DOI: 10.1126/sciadv.1700810
|View full text |Cite
|
Sign up to set email alerts
|

A bimodal activation mechanism underlies scorpion toxin–induced pain

Abstract: A scorpion toxin uses protons in the venom as coactivators to target nociceptive ion channel TRPV1 and cause pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
0
52
0
4
Order By: Relevance
“…As an efficient defensive strategy, toxin-induced TRPV1 activation has been identified in several venomous animals [12][13][14]21,22]. The Chinese bird spider (Ornithoctonus huwena) exploits its bivalent toxin, DkTx, which results in the formation of a stable complex with the TRPV1's outer pore that leads to relentless channel activation and severe pain behavior [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an efficient defensive strategy, toxin-induced TRPV1 activation has been identified in several venomous animals [12][13][14]21,22]. The Chinese bird spider (Ornithoctonus huwena) exploits its bivalent toxin, DkTx, which results in the formation of a stable complex with the TRPV1's outer pore that leads to relentless channel activation and severe pain behavior [14].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that centipede venom could reduce the heat activation threshold of the TRPV1 channel and activate TRPV1 at mammals' physiological body temperatures [12]. In addition, scorpion venom could also target the TRPV1 channel to elicit intense pain in the mildly acidic (pH 6.5) venom environment [21]. Caterpillar venoms are a well-known pain-producing chemical punch.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Die Disulfidbrücken verbinden eine alpha‐Helix mit zwei beta‐Strängen zu einer kompakten Struktur. Entscheidend für die Bindung an den Schmerzrezeptor ist das Lysin an Position 23 (grün) [Abbildungen: (a) nach , (b) mit freundlicher Genehmigung von Jie Zheng, University of California (Davis/USA)].…”
Section: Legendär Schmerzhaftunclassified
“…Jetzt kann das Toxin BmP01 den Kanal aktivieren, indem es ein Proton nachahmt. Dazu bildet es eine Salzbrücke zu E649 aus [Abbildung nach ].…”
Section: Gemeinsam Klappt's Besserunclassified
“…This toxin, found in the venom of Mesobuthus martensii , has a typical inhibitory cysteine knot (ICK) motif structure with three disulfide bonds (1–4, 2–5 and 3–6) stabilizing a compact and rigid protein fold ( Figure 4 ) [ 58 , 59 ]. Within the vast ICK toxins family, BmP01 is further sub-classified as part of the a-KTX8 toxins subgroup with whom it shares similar topology and sequence features [ 60 , 61 ].…”
Section: Bmp01mentioning
confidence: 99%